On Strongly Irregular Points of a Brouwer Homeomorphism Embeddable in a Flow - Zbigniew Leśniak (Abstract and Applied Analysis)
We study the set of all strongly irregular points of a Brouwer homeomorphism f which is embeddable in a flow. We prove that this set is equal to the first prolongational limit set of any flow containing f. We also give a sufficient condition for a class of flows of Brouwer homeomorphisms to be topologically conjugate.